Implementation of Problem Based Learning Model to Improve Understanding of Friday Prayer Material in Elementary School Students - Mahmudi, Ahmad; Suryaningsih, Evi; Rizal, Khairul (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' conceptual understanding of Islamic religious education learning using the problem based learning model. This study uses a type of classroom action research. The design of this study uses the Kemmis & Mctaggart design with four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data were obtained using test and observation techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the problem based learning model can improve student learning outcomes in Islamic religious education learning with the application of audio visual media. This can be seen in cycle I, the average percentage is 50% and in cycle II it is 86%. So it can be stated that student activity developed in cycle II. Improving student learning outcomes through the application of the problem based learning model on Friday prayer material in Elementary Schools was carried out for two cycles. Learning outcomes in cycle I were 66.67% and in cycle II they were 76.67%. So it can be stated that student learning outcomes improved better in cycle II. Based on this, the problem based learning model can be used as one of the media that can be considered by teachers to overcome the problem of low understanding of elementary school students' concepts, especially in Islamic religious education learning.